Dhaba Versus Mutlti Cuisine Restaurants: Dinning Prefernces For Local Food While Travelling Across India (PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Dhabas and multicuisine restaurant play an important role in food business. Preferences of travelers  keeps on changing as per their requirements. Objective: Dhabas and multicuisine restaurants play an important role  in food business. Preferences of travellers keeps on changing as per their requirement. The present study was done  to identify the factor responsible for food tourism and secondly to identify the factors responsible for choosing the  particular food outlet. Methodology: The data for the descriptive research was gathered from people (310) from all over  India. A structured questionnaire with closed ended questions was prepared for survey and distributed to respondents  through digital platform by Google Forms and also through offline mode. Data collection was done in the month of  March-June, 2023. Result: The results revealed many important points for food travellers. Most (52%) of the travellers  loved to dine at Dhaba. People loved to explore new cuisine. People who travels were emotionally attached with the  local food. Further factors responsible for choosing food outlet were unique selling techniques, convenient vehicle  parking, variation in food and beverage and maintaining cuisine authenticity. Cronbach’s alpha value calculated was  found to be 0.0641 which is good and acceptable for the research. Conclusion: Thus study concludes to suggest that  people loves to travel and want to enjoy different flavour of food. Extensive study can be done on any one of the two  objectives achieved in the study.
Keywords: Food; Tourism; Dbabas; Multi-Cuisine Restaurants; Cuisine